2015
DOI: 10.3390/lubricants3040637
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Additives of Coffee Bean Oil in Steel-Steel Contacts

Abstract: Environmental awareness and ever-growing restrictive regulations over contamination have increased the need for more environmentally-friendly lubricants. Due to their superior biodegradability and lower toxicity, vegetable oils are a good alternative to replace currently-used mineral oils. However, vegetable oils show low oxidation and thermal stability and poor anti-wear properties. Most of these drawbacks can be attenuated through the use of additives. In the last decade, ionic liquids have emerged as high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In addition, another degradation peak was observed for SCG at a relatively low temperature of 213 °C, which has not been reported by other researchers (Plaza et al 2012;Li et al 2014). However, Grace et al (2015) studied the thermal degradation of coffee oil, extracted from SCG, with a thermogravimetric analyzer at a heating rate of 10 °C/min in nitrogen environment and found that the degradation of the oil occurs in two steps.…”
Section: Thermal Degradationmentioning
confidence: 70%
“…In addition, another degradation peak was observed for SCG at a relatively low temperature of 213 °C, which has not been reported by other researchers (Plaza et al 2012;Li et al 2014). However, Grace et al (2015) studied the thermal degradation of coffee oil, extracted from SCG, with a thermogravimetric analyzer at a heating rate of 10 °C/min in nitrogen environment and found that the degradation of the oil occurs in two steps.…”
Section: Thermal Degradationmentioning
confidence: 70%
“…In the recent decade, ionic liquids (ILs) have shown great potential as lubricants [6][7][8][9][10][11][12][13][14] or lubricant additives [15][16][17][18][19][20][21][22][23][24][25][26] due to their excellent physicochemical properties [27,28], including low melting point, low flammability, negligible vaper pressure, and high thermal stability. One of the most important characteristics of ILs is that their properties can be tailored by varying the species of the cations and anions, giving rise to numerous families that can be used across different tribological systems.…”
Section: Introductionmentioning
confidence: 99%
“…The samples of IL were prepared for various concentrations of 5%, 3% and 1% by volume. These specific concentrations were chosen in consideration of the fact that the many of the ILs are corrosive in nature above 5% by volume [19]. Calculated amount of IL was blended thoroughly with 10 ml of mineral base oil.…”
Section: Preparation Of Lubricantsmentioning
confidence: 99%
“…The wear scar diameter is measured as the diameter of the impression taken on aluminum foils at various intervals. This method is discussed elsewhere [19]. The wear rate was then calculated using relevant formulae.…”
Section: Preparation Of Lubricantsmentioning
confidence: 99%